An analysis of the potentialities of portuguese vernacular architecture to improve energy efficiency - Fernandes, Jorge Emanuel Pereira (2014)
Vernacular architecture is characterised by a type of formal expression that has been developed in response to a number of factors â climatic, lithologic, cultural and economic â characterising the local area or region. In its various forms, a range of techniques has been employed in different regions to mitigate the effects of climate. Despite the fact that Portugal is a small country, it has a territory full of contrasts, which gave origin to many different architectural manifestations. The approaches adopted in the design and construction of vernacular buildings have the potential for further development and could be adapted in response to contemporary needs. In the future, a blend of tradition and modernity should be aimed at in order to develop a new form of aesthetics and functional construction. Portuguese vernacular architecture is associated with a fund of valuable knowledge that should be studied and aligned with the principles of sustainability. In this paper, is presented the climatic contrast between the northern and southern parts of Portugal and the relation with the purpose of different passive solar techniques used in vernacular architecture to provide comfort. The focus is on the effectiveness of passive cooling techniques (e.g. high thermal inertia, the use of light colours and patios), and the findings of a case study in which the thermal performance during the summer of a vernacular residential building located in the south of Portugal are presented. In the context of the current global drive for clean energy and sustainable buildings, much can be learned from a review of past experience in order to provide an understanding of such forms of construction, which are an intrinsic feature of specific places and have evolved over time in the face of a lack of resources.